The Impact Application of Realistic Mathematics Education on Problem-Solving Ability and Mathematical Communication of Elementary School Students - Ghany Taufik Sidik; Tatang Herman (International Conference on Elementary Education, 2023)
The low achievement of problem-solving and mathematical communication skills of elementary school students in Mathematics lessons is the background of this research. The selection of learning models by teachers is a consideration to minimize and overcome the low problem-solving and mathematical communication skills of students in Elementary School Mathematics. Realistic Mathematics learning efforts are thought to be a teacher's solution to minimize and overcome the low problem-solving and mathematical communication skills of elementary school students in the field of Mathematics. Thus, the researcher's goal is to create this article to review the impact of applying Realistic Mathematics Learning on elementary school students' problem-solving and mathematical communication skills. Researchers use the systematic literature review method. The subject of this study consists of 10 research articles from 2019 to 2022. The technique in this study is the documentation technique. The research instrument is a list of data sequences based on the classification of research materials based on the focus of the study and the format of the record. The results of this study prove that the application of Realistic Mathematics Learning positively impacts elementary school students' problem-solving and mathematical communication abilities.